2007
DOI: 10.1080/03601230701391823
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of fipronil and its enantiomers to marine and freshwater non-targets

Abstract: Fipronil is a phenylpyrazole insecticide used in agricultural and domestic settings for controlling various insect pests in crops, lawns, and residential structures. Fipronil is chiral; however, it is released into the environment as a racemic mixture of two enantiomers. In this study, the acute toxicity of the (S,+) and (R,-) enantiomers and the racemic mixture of fipronil were assessed using Simulium vittatum IS-7 (black fly), Xenopus laevis (African clawed frog), Procambarus clarkii (crayfish), Palaemonetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 23 publications
0
62
0
1
Order By: Relevance
“…Toxicity measurements for the separate enantiomers of chiral pharmaceuticals is the prescribed practice, and such measurements have also been conducted for a few enantiomers of chiral pesticides. [26][27][28] …”
Section: Discussionmentioning
confidence: 98%
“…Toxicity measurements for the separate enantiomers of chiral pharmaceuticals is the prescribed practice, and such measurements have also been conducted for a few enantiomers of chiral pesticides. [26][27][28] …”
Section: Discussionmentioning
confidence: 98%
“…There have been four studies, including the present study, that examined toxicities of fipronil enantiomers to 11 species [21][22][23]. In these 11 species, only two species (Procambarus clarkii and Ceriodaphnia dubia) demonstrated enantioselectivity in toxicities [22,23].…”
Section: Toxicitiesmentioning
confidence: 96%
“…In contrast, Konwick et al [22] demonstrated the S(þ)-enantiomer was significantly more toxic to Ceriodaphnia dubia than either the R(À)-enantiomer or racemate. Overmyer et al [23] examined the toxicities of fipronil enantiomers to six marine and freshwater species and found that only crayfish (Procambarus clarkii) demonstrated a statistically significant difference in toxicity between the two enantiomers. These studies indicate that enantiomer-specific toxicity varies with species.…”
Section: Introductionmentioning
confidence: 98%
“…In theory, enantiomers have identical physical and chemical properties and abiotic degradation rates (Garrison et al, 1996), whereas their individual toxicity, biological activity, and microbial degradation rates have been shown to differ (Overmyer et al, 2007;Diao et al, 2010;Liu et al, 2012;Sun et al, 2012). Several studies have reported that ethofumesate enantiomers showed an enantioselectivity in biochemical processes.…”
Section: Introductionmentioning
confidence: 99%